Analysis of Oil Losses on Empty Bunch Press Using The Statistical Process Control (SPC) Method at PT. XYZ - Azelia Puteri; Ema Lestari; Titis Linangsari; Fatimah; Jaka Darma Jaya; Nuryati Nuryati (Jurnal Teknologi Agro-Industri, 2025)
PT. XYZ is a palm oil processing enterprise.  The products produced are crude palm oil (CPO) and palm kernel oil (PKO).  The level of oil loss in PT. XYZ Empty Bunch Press should not exceed 0.90%, but there has been a significant increase in the last three months, exceeding the company's guidelines.  This disease may have an impact on CPO production output.  As a result, this study was done to investigate oil loss in empty bunch presses.  The method employed is Statistical Process Control (SPC), which employs three tools: a checksheet, histogram for data distribution, and fishbone diagram to aid in understanding and fixing the problems encountered.  The largest oil loss is 1.56%, which surpasses the Company's requirement of 0.9%. In order to achieve the required standards, suggestions for improvement must be made using a fishbone diagram that incorporates human, machine, method, and raw material aspects.